Effects of Gnaphalium affine D. Don on hyperuricemia and acute gouty arthritis. (5th May 2017) - Zhang, Hong-jian; Li, Ling-nan; Zhou, Jie; Yang, Qin-qin; Liu, Pei-gang; Xu, Pan; Liang, Wei-qing; Cheng, Lin; Zhang, Ying-qi; Pu, Jin-bao; Hu, Yi-juan
Abstract: Ethnopharmacological relevance: The Gnaphalium affine D. Don is used in China as a folk medicine to treat gout, anti-inflammatory, antitussive and expectorant activities. The aim of this study was to evaluate the potential of the extract of G. affine to treat hyperuricemia and acute gouty arthritis in animal model. Materials and methods: G. affine extract was evaluated in an experimental model with potassium oxonate (PO) induced hyperuricemia in mice which was used to evaluate anti-hyperuricemia activity and xanthine oxidase (XO) inhibition. Therapies for acute gouty arthritis was also investigated on monosodium urate (MSU) crystal induced paw edema model. Results: G. affine extract showed expressive results on active in reducing serum uric acid (Sur) through effect renal mGLUT9 and mURAT1 mainly and inhibit XO activity in vivo . The extract of G. affine also showed significant anti-inflammatory activity and reduced the paw swelling on MSU crystal-induced paw edema model. Meanwhile, eight major compounds were identified by HPLC-ESI-QTOF-MS/MS. Conclusions: The extract of G. affine showed significant effect on evaluated models and therefore may be active agents for the treatment of hyperuricemia and acute gouty arthritis. Graphical abstract: